THE EFFECTIVENESS OF INFORMATION SERVICES USING THE JIGSAW COOPERATIVE LEARNING MODEL TO INCREASE STUDENT SELF ESTEEM - Anna Ismawati; Dina Sukma; Yarmis Syukur; Nurfarhanah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to test the effectiveness of information services using the jigsaw cooperative learning model to increase student self-esteem. This type of research is Quasi Experiment Design. The sample was selected using a purposive sampling technique. The sample in this study were 60 students who were divided into two classes. The research instrument used was the Likert Scale model, the data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov 2 Independent Samples. The research results show that; (1) There is a significant difference in the self-esteem of the experimental group students before and after participating in information services using the jigsaw type cooperative learning mode, the probability score is below alpha 0.05 (0.000 <0.05), (2) there is a difference in the self-esteem of the group students control before and after participating in information services without using the jigsaw cooperative learning model obtained a probability number below alpha 0.05 (0.000 <0.05), (3) there was a difference in the self-esteem of the experimental group students who were given information services using the cooperative learning type jigsaw with the control group that was given information services without using the jigsaw type of cooperative learning model was obtained at 0.014 or probability below 0.05 (0.014 <0.05), the difference can be seen from the posttest results of the experimental group which are higher than the posttest results of the control group. From these findings it can be concluded that information services using the jigsaw cooperative learning model are more effective in increasing students' self-esteem.